The gender wage gap in the French veterinary labor market - Berrada, Mehdi; Ndiaye, Youba; Raboisson, Didier; Lhermie, Guillaume (Frontiers in Veterinary Science, 2022)
Among the most important recent changes in the veterinary profession is the increasing percentage of women. Understanding trends driving the veterinary labor market is important to enable leaders in the veterinary profession and policy makers to plot strategic actions that will improve the profession. The objective of this paper was to estimate the gender pay gap in the veterinary labor market. We analyzed data from an anonymous online survey conducted in France in 2021 by the veterinary practitioner union. We assessed the gender gap pay using two regression approaches, ordinary least squares method and Blinder-Oaxaca decomposition, while controlling for all other variables (ceteris paribus). We provided evidence that male veterinarians earned wages approximately 9.3% higher (controlling for all other variables). This difference represented the “unexplained variance” that may be due to gender discrimination or unobserved characteristics.